2018
DOI: 10.1016/j.nrjag.2018.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Application of geoelectrical measurements for detecting the ground-water seepage in clay quarry at Helwan, southeastern Cairo, Egypt

Abstract: Clay is considered one of the most important raw materials in cement industry. It is the most common rich source of silica and alumina. During the quarrying process a few months later, a new feature of water accumulation appeared on the quarry floor and many water pools were formed during excavation process. In order to detect the source and extension of the groundwater seepage, geoelectrical resistivity technique in the form of vertical electrical soundings was applied. Fifteen vertical electrical soundings w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Interpretation of geological data was necessary for translating quantitative value into an available and realistic picture of the Geological sense [19]. After knowing the wellborehole rock lithology, the next step is to connect between measurement points to produce a vertical cross-section along the cross-sectional direction.…”
Section: Methodsmentioning
confidence: 99%
“…Interpretation of geological data was necessary for translating quantitative value into an available and realistic picture of the Geological sense [19]. After knowing the wellborehole rock lithology, the next step is to connect between measurement points to produce a vertical cross-section along the cross-sectional direction.…”
Section: Methodsmentioning
confidence: 99%
“…As the basis for data interpretation, open sinkhole references are used in the form of springs located on paths 1 and 6 and low resistivity anomalies to characterize karst aquifers. Generally, resistivity values are classified into three zones [32][33][34][35][36]. The measurement results obtained resistivity anomalies between 1.2 m to 485 m and were classified as shown in Table 1.…”
Section: Identification Of Sub-surface Bedding Patternsmentioning
confidence: 99%
“…While in the eastern part with lines 2, 4, and 5 are interpreted as massive limestone. Several authors have suggested that massive limestones dominate the high resistivity with depths between 25-40 m [33,34,[37][38][39].…”
Section: High Resistivity Zonementioning
confidence: 99%
“…GPR is a current surface geophysical survey technique that has advanced significantly in the past 30 years for shallow and highly accurate exploration; it is also safe for use in urban environments to identify buried objects and determine the subsurface structure and properties [15]. It is the most widely used technique for shallow subsurface investigation [16,17], geotechnical investigation [18,19], archaeology [20,21], underground structural exploration on the Moon [22,23] and Mars [24], environmental and engineering studies [7,25,26] for detecting water leaks around artificial buildings, and the detection of subsurface utilities [27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%